1994
DOI: 10.1002/app.1994.070540612
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate properties of epoxy resins modified with a polysiloxane–polycaprolactone block copolymer

Abstract: SYNOPSISMechanical and fracture mechanics properties of transparent multiphase epoxy resins toughened with various amounts of compatibilized silicone liquid rubbers consisting of polycaprolactone-block-poly ( dimethylsiloxane ) -block-polycaprolactone triblock copolymer have been investigated. At silicone liquid rubber contents < 10 wt % significantly improved toughness has been achieved without adversely affecting thermal and mechanical properties. Fractographic and interferometric methods have been applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 4 publications
0
47
0
Order By: Relevance
“…53 Such copolymer having controlled structure can be successfully used as toughening agents. [53][54][55] Konzol et al 56 have reported that the miscibility of PDMS can be increased by introducing polycaprolactam (PCL) block into PDMS. Hydroxyl-terminated block copolymers having basic structure (PCL) 2 -b-PDMS-b-(PCL) 2 with controlled composition leads to phase separated system with uniformly dispersed elastomeric particles in the order of magnitude of 20 nm.…”
Section: Saturated Liquid Rubbersmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Such copolymer having controlled structure can be successfully used as toughening agents. [53][54][55] Konzol et al 56 have reported that the miscibility of PDMS can be increased by introducing polycaprolactam (PCL) block into PDMS. Hydroxyl-terminated block copolymers having basic structure (PCL) 2 -b-PDMS-b-(PCL) 2 with controlled composition leads to phase separated system with uniformly dispersed elastomeric particles in the order of magnitude of 20 nm.…”
Section: Saturated Liquid Rubbersmentioning
confidence: 99%
“…57 Incorporation of about 5% of such modifier resulted in the two-fold increase in toughness. 56,57 Recently Tog et al 58,59 showed that the miscibility of PDMS with epoxy can be improved by grafting the PDMS with glycidyl methacrylate (GMA). The graft segments of PMMA and PGMA on the surfaces of siloxane particles enhance their compatibility with the epoxy and ensure homogeneous distribution of particles leading to an effective toughening effect.…”
Section: Saturated Liquid Rubbersmentioning
confidence: 99%
“…6 To improve the compatibility of polysiloxane with epoxy matrix, a great deal of researches have been conducted, including using silane coupling agents, 7,8 utilizing modified PDMS (such as capped with amino, 9,10 epoxy 11,12 and isocyanate group 13 ), making use of sol-gel method to bridge polysiloxane and epoxy monomers, 14 and adding block containing silicone to make polysiloxane homogeneously dispersed in the matrix. [15][16][17] Nevertheless, the flexibility of modified epoxy resin is influenced by many factors, such as the particle size, distribution, and the content of elastomer in the epoxy resin matrix. [18][19][20][21] Introduction of predispersed polysiloxane particles into modify epoxy resin can keep the size of paticles stable before and after curing, which may be a good attempt to improve the toughness of the epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, examples of nanomaterials with more classic applications are related to the improvement of mechanical properties in thermosetting materials. [4][5][6][7] Block copolymers are a popular class of nanomaterials known to self-assemble into nanoscale ordered structures in bulk as well as in solution. Recently, it has been discovered that block copolymers are not only dispersible in epoxy resins but also capable of ordering epoxy networks at the nanometer scale in both cured and uncured states.…”
Section: Introductionmentioning
confidence: 99%